Synthesis of poly((2-dimethylamino)ethyl methacrylate) via atom transfer radical polymerization and surface characterization by inverse gas chromatography - Dasdan, D. S. (BULGARIAN ACAD SCIENCE, 2016)
Poly(2-dimethylamino) ethyl methacrylate) (PDMAEMA) was synthesized via atom transfer radical polymerization. The synthesized PDMAEMA was characterized by FTIR, GPC and DSC. The inverse gas chromatography technique was used to obtain the surface properties of PDMAEMA. The retentions of nonpolar solvents such as n-hexane, nheptane, n-octane, n-nonane, n-decane and other acidic, basic and amphoteric probes such as tetrahydrofurane, dichloromethane, chloroform, acetone, ethyl acetate and benzene used without further purification on PDMAEMA were measured in the temperature ranges from 303 to 373 K by inverse gas chromatography (IGC). The dispersive component of the surface energy, gamma(D)(S) of studied adsorbent surface was estimated using retention times of different nonpolar organics in the infinite dilution region. Dispersive components of the surface energies, gamma(D)(S). according to Fowkes and Dorris-Gray approaches and the acid, K-A and base, K-D constants for PDMAEMA were calculated.
Keywords: Poly(2-dimethylamino)ethyl methacrylate); Inverse gas chromatography; Surface and adsorption properties; Surface free energies; Lewis acid-base constants; ACID-BASE; Chemistry